TRANSFORMASI PEMASARAN PRODUK HALAL: STRATEGI DIGITAL BERBASIS PRINSIP EKONOMI ISLAM BAGI UMKM DI SIDOARJO - Zujajatul 'Ilmi; Adinugroho, Mukhtar; Utami, Hapsari Wiji (ITB AAS INDONESIA Surakarta, 2025)
This study aims to analyze the transformation of halal product marketing among Micro, Small, and Medium Enterprises (UMKM) in Sidoarjo Regency through the implementation of digital strategies based on Islamic economic principles. The background of this research lies in the rapid growth of the halal industry in Indonesia and the crucial role of UMKM in supporting local economic development. However, the adoption of sharia-compliant digital marketing still faces several obstacles, including limited digital literacy and a lack of understanding of Islamic principles in marketing practices. This research employs a qualitative descriptive approach with purposive sampling to determine informants, specifically halal UMKM actors who have utilized digital media for at least six months. Data were collected through in-depth interviews, participatory observation, and documentation of digital marketing activities. The data were analyzed using qualitative descriptive techniques, consisting of data reduction, data presentation, and conclusion drawing. The validity of the data was ensured through triangulation and the application of trustworthiness criteria. The findings reveal that most halal UMKM in Sidoarjo have used social media and marketplaces as their main promotional tools. The application of Islamic economic principles such as honesty, trustworthiness, and transparency has begun to be integrated, although not yet systematically structured within digital strategies. The main challenges include limited knowledge of sharia-based digital marketing, human resource constraints, and the lack of training and mentoring. Nevertheless, digital marketing has proven to increase sales, expand market reach, and strengthen the halal image of products. This study proposes a halal digital marketing strategy model emphasizing trading as an act of worship, product information transparency, Islamic content, halal payment systems, and consistent service.